'Mediterraneo baltico': Italian Fascist propaganda in Finland (1933–9). Issue 4 (November 2020) - Ferrarini, Fabio
Abstract : This article focuses on Italian Fascist propaganda in Finland. Federico Finchelstein (2010) characterised fascism as a global-transnational doctrine with diverse reformulations, ramifications and permutations. Therefore, the Finnish case-study is useful in the analysis of Mussolini's twin struggle against Soviet Communism and the increasing Nazi threat in the Baltic in the 1930s and 1940s. This article will examine how Mussolini tried to keep in touch with Finnish fascists after Hitler's rise to power. Organisations and groups like the Lapua Movement and the Finnish Patriotic People's Movement were inspired by Italian Fascism and the success of the March on Rome encouraged their hope that they could take power in Finland. The ultimate failure of Finnish fascism has ensured the continued marginalisation of fascism as a research subject in the Finnish academic tradition. Yet, as Roger Griffin suggests, studies of peripheral and failed fascisms can also contribute important insights for understanding both the 'centre' of fascism, as well as modern nationalist extremist movements. Fascism as an international political phenomenon cannot be understood from rigidly national interpretative frameworks.